Behavior of stroke volume variation in hemodynamic stable patients during thoracic surgery with one-lung ventilation periods - Tome,María Lema (2018)
Abstract Introduction: In last few years, emphasis was placed in goal-directed therapy in order to optimize patient's hemodynamic status and improve their prognosis. Parameters based on the interaction between heart and lungs have been questioned in situations like low tidal volume and open chest surgery. The goal of the study was to analyze the changes that one-lung ventilation can produce over stroke volume variation and to assess the possible impact of airway pressures and lung compliance over stroke volume variation. Methods: Prospective observational study, 112 patients undergoing lung resection surgery with one-lung ventilation periods were included. Intravenous fluid therapy with crystalloids was set at 2 mL.g-1. Hypotension episodes were treated with vasoconstrictive drugs. Two-lung Ventilation was implemented with a TV of 8 mL.g-1 and one-lung ventilation was managed with a TV of 6 mL.g-1. Invasive blood pressure was monitored. We recorded the following cardiorespiratory values: heart rate, mean arterial pressure, cardiac index, stroke volume index, airway peak pressure, airway plateau pressure and static lung compliance at 3 different times during surgery: immediately after lung collapse, 30 min after initiating one-lung ventilation and after restoration of two-lung ventilation. Results: Stroke volume variation values were influenced by lung collapse (before lung collapse 14.6 (DS) vs. OLV 9.9% (DS), p < 0.0001); or after restoring two-lung ventilation (11.01 (DS), p < 0.0001). During two-lung Ventilation there was a significant correlation between airway pressures and stroke volume variation, however this correlation lacks during one-lung ventilation. Conclusion: The decrease of stroke volume variation values during one-lung ventilation with protective ventilatory strategies advices not to use the same threshold values to determine fluid responsiveness.